Vertebral Artery Thrombosis in Chronic Idiopathic Thrombocytopenic Purpura - Zakaria Hindi; Nirmal Onteddu; Christopher A. Ching; Abdallah A. Khaled (Case Reports in Hematology)
Introduction. Immune thrombocytopenic purpura (ITP) is an autoimmune hematological disorder that causes decreased production and destruction of platelets leading to thrombocytopenia. Although thrombocytopenia usually causes hemorrhagic problems, thrombotic events like strokes, although rare, can still occur. Management of thrombotic events in patients with ITP differs from that of patients with normal platelet count function and count. Case Description. A 32-year-old female with a history of ITP presented with ischemic stroke. The patient was treated in the hospital with IV immunoglobulin, discharged to a rehabilitation facility, and had complete resolution of symptoms when examined at a follow-up visit 3 months later. Conclusion. Although stroke in patients with ITP is very rare due to thrombocytopenia, it has been reported in several other published cases and is likely associated with increased platelet microparticle levels, a byproduct of platelet destruction. While usage of antiplatelet therapy in such patients is debated, immunosuppression therapy has been the mainstay treatment in all published cases.